Degradation of carbonated reactive MgO-based concrete exposed to nitric acid - Muthu Murugan (2021)
MgO cement (RMC)-based mixes are known to gain strength via carbonation. While the strength gain mechanism of RMC mixes has been studied, their durability under aggressive environments is relatively unknown. This study investigated the changes in the performance and microstructure of two concrete formulations, whose binder component was made up of RMC with and without 50 % FA substitution. These concrete specimens were initially carbonated for 28 days to gain strength, followed by immersion in 0.5»M nitric acid for 14 days. The degradation of both specimens was recorded in terms of changes in their strength, mass, composition and microstructure. The use of FA led to a lower hydration and subsequent carbonation due to the lower RMC content, thereby limiting initial strength development. While the leaching of Mg-based phases into the external solution was recorded, most hydrate and carbonate phases were still present after acid exposure. The ∼56 % reduction in strength experienced by both specimens was accompanied with the formation of micro cracks.